Photo-Induced Protein Oxidation: Mechanisms, Consequences and Medical Applications - Fuentes-Lemus, E; Fuentes-Lemus, E (Portland Press Ltd, 2020)
Irradiation from the sun has played a crucial role in the origin and evolution of life on the earth. Due to the presence of ozone in the stratosphere most of the hazardous irradiation is absorbed, nonetheless UVB, UVA, and visible light reach the earth s surface. The high abundance of proteins in most living organisms, and the presence of chromophores in the side chains of certain amino acids, explain why these macromolecules are principal targets when biological systems are illuminated. Light absorption triggers the formation of excited species that can initiate photo-modification of proteins. The major pathways involve modifications derived from direct irradiation and photo-sensitized reactions. In this review we explored the basic concepts behind these photochemical pathways, with special emphasis on the photosensitized mechanisms (type 1 and type 2) leading to protein oxidation, and how this affects protein structure and functions. Finally, a description of the photochemical reactions involved in some human diseases, and medical applications of protein oxidation are presented. ©2020 The Author(s).